Hearing impairment in patients of hypothyroidism in sub Himalayan region - Gupta, Vikasdeep; Dogra, Sunder Singh; Bansal, Pardeep; Thakur, Kuldeep; Sharma, Vidhu; Verma, Deepak; ., Vandana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The objective of the study was to assess the hearing impairment in patients of hypothyroidism. Methods: A prospective clinical study has done at a referral centre included 33 diagnosed patients of hypothyroidism in the age group of 15 to 65 years, fulfilling the inclusion and exclusion criteria who attended the outpatient department. The diagnosis of hypothyroidism was confirmed by thyroid function tests i.e., serum T3, T4 and TSH levels while hearing assessment was done using tuning fork tests, pure tone audiometry, impedance audiometry and otoacoustic emissions. Hearing impairment was measured in decibels of hearing loss, or dB HL and graded as mild, moderate, moderately severe, severe, or profound. Results: Percutaneous transluminal angioplasty showed 42.7% of the patients had high frequency sensorineural type of hearing loss. The air bone gap was not significant. On tympanometry, all the patients had type A graph and distortion product otoacoustic emissionss in all patients were pass. Conclusions: Acquired hypothyroidism affects primarily high frequency hearing thresholds causing high frequency sensorineural hearing loss, with little or no effect on lower frequencies.